2021
DOI: 10.3390/ijerph18105062
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution, Neonatal Immune Responses, and Potential Joint Effects of Maternal Depression

Abstract: Prenatal maternal exposure to air pollution may cause adverse health effects in offspring, potentially through altered immune responses. Maternal psychosocial distress can also alter immune function and may increase gestational vulnerability to air pollution exposure. We investigated whether prenatal exposure to air pollution is associated with altered immune responses in cord blood mononuclear cells (CBMCs) and potential modification by maternal depression in 463 women recruited in early pregnancy (1999–2001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Previous studies found decreased IL‐10 production in cord blood from newborns whose mothers were exposed to moderate concentrations of PM 2.5 during pregnancy 13 and low PM 10 levels in the last week of gestation 15 . However, a study conducted in three Bulgarian cities with differential particulate matter concentrations showed increased IL‐10 concentrations in adolescents living in the higher polluted area 43 .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Previous studies found decreased IL‐10 production in cord blood from newborns whose mothers were exposed to moderate concentrations of PM 2.5 during pregnancy 13 and low PM 10 levels in the last week of gestation 15 . However, a study conducted in three Bulgarian cities with differential particulate matter concentrations showed increased IL‐10 concentrations in adolescents living in the higher polluted area 43 .…”
Section: Discussionmentioning
confidence: 91%
“…10,35 Exposure to air pollution is suggested to induce reactive oxygen species (ROS) generation that leads to increase production of pro-inflammatory cytokines. 36 Although Hanh et al 15 found prenatal exposure to moderate PM 2.5…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations